Science and religion: Steps toward an analytical framework within contemporary science studies - Silke Gülker (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2012)
The relationship between science and religion was one of the most important topics in the era when sociology was founded but it has since disappeared from the empirical science studies agenda almost completely. This paper argues for reopening the debates on these issues and develops a preliminary framework for empirical analysis. This involves describing science as a context of discovery, justification, and persuasion; religion is seen in terms of organization, individual faith, and as (a part of) culture. Regarding all the dimensions, this paper discusses which questions should guide the investigation of the relationship between science and religion from the perspective of contemporary science studies. – – Das Verhältnis von Wissenschaft und Religion war eines der zentralen Themen bei Gründung der Soziologie und ist im Laufe der Jahrzehnte von der Agenda der empirischen Wissenschaftsforschung weitgehend verschwunden. Das Papier argumentiert für eine Wiederaufnahme der Debatten zu diesem Thema und entwickelt einen ersten Bezugsrahmen für empirische Analysen. Dafür wird Wissenschaft als Entdeckungs-, Rechtfertigungs- und Überzeugungskontext beschrieben und Religion als Organisation, als (Teil von) Kultur und als individueller Glaube. Für die jeweiligen Dimensionen wird reflektiert, welche Fragestellungen eine Untersuchung des Verhältnisses von Wissenschaft und Religion aus Perspektive der aktuellen Wissenschaftsforschung leiten sollten.
Keywords: 300